Muslim Intellectual Deficit - Ashaq Hussain (International Institute of Islamic Thought, 2019)
It is no exaggeration to say that some of the greatest intellectual movements in the annals of human civilization were launched under the aegis of Islam. Islamic contributions to the promotion of knowledge and learning are noteworthy. Franz Rosenthal, for one, perceptively observed that Islam’s lasting and invaluable gift to humankind is that it made the hidden treasures of knowledge available to all sectors of society. The intellectual revolution ushered in under the direction of Islamic civilization blossomed and came to fruition through the central importance attached to the arts of language. (The earliest verses of the Qur’an revealed to the Prophet, for example, highlighted their crucial significance.) The importance attached to learning and the transmission and dissemination of knowledge was institutionalized through a wide network of schools, colleges, universities, libraries, observatories, and medical residencies in the Islamic world. The selfless devotion of individual scholars, the munificence of private donors, waqf endowments, and royal patronage played a central role in the inception and maintenance of these institutions. For Muslim intellectuals, the question of intellectual decay has long been worrying, yielding repeated efforts to analyze and diagnose the historical and spiritual factors responsible for the stagnation and decline of the Muslim world. Parray’s introduction highlights Qur’anic terms key to his effort, including furqān (distinction), dhikr (remembrance), and hudā (guidance), which also signal how he reads the scripture. He quotes Mustansir Mir, renowned Pakistani expert on Qur’anic studies, who says of the various aspects under which the Qur’an presents itself, that these names “not only represent so many facets of the Islamic scripture, but they also make up, when seen as inter-related and inter-connected, a coherent and ...